Index of Residential Development: Evaluation of the Possibility of New Residential Construction Depending on the City Plan - Vařbuchta, Petr; Hromádka, Vít (MDPI, 2023)
This article focuses on the issue of the urban development of cities and their residential development from the perspective of spatial planning. Spatial planning fundamentally determines what kind of construction is feasible in cities. However, spatial plans often do not consider spatial limits, which often go against the proposed ways of using the given sites, or make their use fundamentally difficult, for example, by disproportionately increasing of the costs of residential construction, when it is necessary to remediate old burdens in the defined locality. The subject of the presented research was to examine the possibility of establishing an Index of Residential Development (IoRD), which evaluates the possibilities of residential development in the territory of urban agglomerations. The aim of the research, in the form of establishing of an Index of Residential Development (IoRD), was to assess how it is possible to consider spatial limits associated with residential construction in urban intravilanes in order to identify the objectives of further spatial development planned by cities. Subsequently, the partial aim of the research was also to create a usable tool for support in the decision making of development organizations on the location of their project in a given space. Based on the results of the research, it was deduced that the limits associated with the residential development in intravilanes based on the IoRD could be considered. Clear links were also shown between the limits in the territory and the impaired possibility of construction in cities with zoning plans, which did not respond to the limits in the territory by adding other design zones, or completely ignored them. Although the methodology for determining of the Index of Residential Development (IoRD) was verified due to the availability of data in the case study carried out in the Czech Republic city of Brno, the methodology is applicable to any urban agglomeration even outside the Czech Republic when fulfilling the conditions defined in the article.

This article focuses on the issue of the urban development of cities and their residential development from the perspective of spatial planning. Spatial planning fundamentally determines what kind of construction is feasible in cities. However, spatial plans often do not consider spatial limits, which often go against the proposed ways of using the given sites, or make their use fundamentally difficult, for example, by disproportionately increasing of the costs of residential construction, when it is necessary to remediate old burdens in the defined locality. The subject of the presented research was to examine the possibility of establishing an Index of Residential Development (IoRD), which evaluates the possibilities of residential development in the territory of urban agglomerations. The aim of the research, in the form of establishing of an Index of Residential Development (IoRD), was to assess how it is possible to consider spatial limits associated with residential construction in urban intravilanes in order to identify the objectives of further spatial development planned by cities. Subsequently, the partial aim of the research was also to create a usable tool for support in the decision making of development organizations on the location of their project in a given space. Based on the results of the research, it was deduced that the limits associated with the residential development in intravilanes based on the IoRD could be considered. Clear links were also shown between the limits in the territory and the impaired possibility of construction in cities with zoning plans, which did not respond to the limits in the territory by adding other design zones, or completely ignored them. Although the methodology for determining of the Index of Residential Development (IoRD) was verified due to the availability of data in the case study carried out in the Czech Republic city of Brno, the methodology is applicable to any urban agglomeration even outside the Czech Republic when fulfilling the conditions defined in the article.
Index of Residential Development: Evaluation of the Possibility of New Residential Construction Depending on the City Plan
Keywords: Index of Development; Index of Residential Development; urban planning; spatial planning; city plan; residential housing; Index of Development; Index of Residential Development; urban planning; spatial planning; city plan; residential housing